A revision of the Nearctic species of the genus Stethusa Casey, 1910 (Coleoptera: Staphylinidae: Aleocharinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
The Nearctic and Neotropical genus Stethusa Casey, 1910 is redescribed. Descriptions and a key to the three valid Nearctic species of Stethusa (S. dichroa (Gravenhorst, 1802), S. klimschi (Bernhauer, 1909), and S. spuriella (Casey, 1910)) are provided. Atheta affluens Casey, 1910, At. irvingi Casey, 1910, At. galvestonica Casey, 1910, At. canonica Casey, 1910, At. sagax Casey, 1910, At. sororella Casey, 1910, At. clarescans Casey, 1911a, At. videns Casey, 1911a, At. cynica Casey, 1911a, At. cernens Casey, 1911a, At. officiosa Casey, 1911a, At. tuta Casey, 1911a, Dimetrota novella Casey, 1910 and D. sentiens Casey, 1910 are placed in synonymy with Stethusa dichroa. Atheta unigranosa Bernhauer, 1909 (nec 1908), At. subdebilis Casey, 1910, At. duplicata Fenyes, 1920 and At. macrops Notman, 1920 are synonymized with S. spuriella (Casey, 1910). Neotropical At. lurida (Erichson, 1839) and At. luederwaldti Bernhauer, 1908 are transferred to Stethusa. Atheta texana Casey, 1910, At. crenuliventris Bernhauer, 1907 and At. iheringi Bernhauer, 1908 do not belong to Stethusa. Atheta mendosa Casey, 1910 is placed in synonymy with At. texana Casey, 1910. Dimetrota bradorensis Lohse, 1990 is synonymized with At. crenuliventris Bernhauer, 1907. Lectotypes are designated for Aleochara dichroa Gravenhorst, 1802, Atheta crenuliventris Bernhauer, 1907, At. luederwaldti Bernhauer, 1908, At. iheringi Bernhauer, 1908, At. unigranosa Bernhauer, 1909, At. affluens Casey, 1910, At. irvingi Casey, 1910, At. galvestonica Casey, 1910, At. canonica Casey, 1910, At. sagax Casey, 1910, At. sororella Casey, 1910, At. spuriella Casey, 1910, At. subdebilis Casey, 1910, At. texana Casey, 1910, At. clarescans Casey, 1911a, At. cynica Casey, 1911a, At. cernens Casey, 1911a, At. officiosa Casey, 1911a, Dimetrota novella Casey, 1910 and D. sentiens Casey, 1910.